Endometrial glycogen metabolism during early pregnancy in mice. Issue 9 (17th July 2022) - Chen, Ziting; Sandoval, Kassandra; Dean, Matthew
Abstract: Glucose is critical during early pregnancy. The uterus can store glucose as glycogen but uterine glycogen metabolism is poorly understood. This study analyzed glycogen storage and localization of glycogen metabolizing enzymes from proestrus until implantation in the murine uterus. Quantification of diastase‐labile periodic acid–Schiff (PAS) staining showed glycogen in the glandular epithelium decreased 71.4% at 1.5 days postcoitum (DPC) and 62.13% at DPC 3.5 compared to proestrus. In the luminal epithelium, glycogen was the highest at proestrus, decreased 46.2% at DPC 1.5 and 63.2% at DPC 3.5. Immunostaining showed that before implantation, glycogen metabolizing enzymes were primarily localized to the glandular and luminal epithelium. Stromal glycogen was low from proestrus to DPC 3.5. However, at the DPC 5.5 implantation sites, stromal glycogen levels increased sevenfold. Similarly, artificial decidualization resulted in a fivefold increase in glycogen levels. In both models, decidualization increased expression of glycogen synthase as determine by immunohistochemistry and western blot. In conclusion, glycogen levels decreased in the uterine epithelium before implantation, indicating that it could be used to support preimplantation embryos. Decidualization resulted in a dramatic increase in stromal glycogen levels, suggesting it may have an important, but yet undefined, role in pregnancy.